2017
DOI: 10.1097/ede.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Recall of Pregnancy-related Events

Abstract: Background Early-life factors can be associated with future health outcomes and are often measured by maternal recall. Methods We used data from the North Carolina Early Pregnancy Study and Follow-up to characterize long-term maternal recall. We used data from the Early Pregnancy Study as the gold standard to evaluate the accuracy of pre-pregnancy weight, early pregnancy behaviors, symptoms and duration of pregnancy, and child’s birthweight reported at follow-up, for 109 women whose study pregnancies had res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…However, previous studies pointed out that these variables, as well as birthweight and gestational age, were reported accurately 20 years after birth. 58,59 The FFQ used to assess dietary intake of the previous year could also involve recall bias although this tool has been used widely in nutrition epidemiology, allowing classification according to diet exposure level. [60][61][62] The dichotomization of the dietary pattern scores and the consequent reduction of statistical power should be another limitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies pointed out that these variables, as well as birthweight and gestational age, were reported accurately 20 years after birth. 58,59 The FFQ used to assess dietary intake of the previous year could also involve recall bias although this tool has been used widely in nutrition epidemiology, allowing classification according to diet exposure level. [60][61][62] The dichotomization of the dietary pattern scores and the consequent reduction of statistical power should be another limitation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that among women with GN, those who experienced worsening kidney function, increasing proteinuria, worsening blood pressure control, and/or preeclampsia during prior pregnancy were diagnosed with GN sooner than their counterparts without these pregnancy complications. Although we considered recall bias as a potential explanation for this difference (i.e., women newly diagnosed with GN recall recent pregnancy complications more readily), literature suggests that maternal recall of even distant pregnancy events is generally accurate,6, 7 and recent validation of the question “Did you have a hypertensive disorder in pregnancy?” in a Dutch population of women was found to be 84% sensitive and 94% specific when compared to medical chart review 8 . In our study, pregnancies with reported renal-relevant complications were also objectively more likely to deliver prematurely with a lower mean birth weight, disputing recall bias as the sole explanation for the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is possibility that women could selfreport pre-pregnancy weight with reasonable accuracy almost 30 years later (24) , the recall of maternal prepregnancy BMI implies recall bias that should be considered a limitation of the present study. Additionally, our small and homogenous sample, composed of young, apparently healthy and educated women (and their mothers), implies limitation regarding external validity; that is, generalisation of our results to different samples with different characteristics is not appropriate.…”
Section: Strengths and Limitationsmentioning
confidence: 87%